Flexible terahertz beam manipulation and convolution operations in light-controllable digital coding metasurfaces - Min Jia; Chao Zhao; Hui Wang; Weiran Sun; Yuncheng Lu (iScience)
Summary: The development of coding metasurface opens an important development direction for beam modulator components. However, the lack of dynamic tunability is a major obstacle to the development and practicality of terahertz coding metasurface. In this work, we design and implement a wireless optically controlled tunable coding metasurface by integrating photosensitive silicon into the metasurface, which realizes the ultra-fast dynamic switching effect of terahertz beam and dynamic convolution operation of 2-bit coding metasurface. We also achieve dynamic modulation of vortex electromagnetic waves based on wireless light-controllable coding metasurfaces. And the genetic algorithm is used to reverse design the array arrangement of the coding metasurface to achieve terahertz broadband radar scattering cross-section reduction. The proposed optically controlled dynamic metasurface developed in this study has the potential to create non-contact metasurfaces, thereby making it a valuable tool for future practical applications.